2017
DOI: 10.1007/s00299-017-2204-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of oxidative status in three native Australian species during cold acclimation and cryopreservation

Abstract: Three wild species exhibited a significant reduction in antioxidants throughout the cryopreservation protocol, whilst the half-cell reduction potential became more oxidised. Antioxidant content recuperated in recovering shoot tips. Cryopreservation is the most efficient and cost-effective long-term storage solution for the conservation of a wide range of plant species and material. Changes in the levels of antioxidants during the process of cryopreservation are known to reduce post-cryogenic survival due to ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Although antioxidants within the cells can balance the build-up of ROS (Mittler 2002), it has been shown that concentrations of antioxidants like glutathione (GSH) and ascorbic acid (AsA) decrease in plant tissues with each successive step of the cryopreservation process (Fig. 4) (Funnekotter et al 2017b). Although Chen et al (2015) also found a reduction in GSH and AsA antioxidants in thawing and recovery stages, levels of these antioxidants were found to increase in the desiccation period.…”
Section: Role Of Antioxidantsmentioning
confidence: 98%
See 4 more Smart Citations
“…Although antioxidants within the cells can balance the build-up of ROS (Mittler 2002), it has been shown that concentrations of antioxidants like glutathione (GSH) and ascorbic acid (AsA) decrease in plant tissues with each successive step of the cryopreservation process (Fig. 4) (Funnekotter et al 2017b). Although Chen et al (2015) also found a reduction in GSH and AsA antioxidants in thawing and recovery stages, levels of these antioxidants were found to increase in the desiccation period.…”
Section: Role Of Antioxidantsmentioning
confidence: 98%
“…Cryopreservation is a multi-step process, involving (i) the initial excision of the germplasm such as seed embryos or shoot tips to obtain sufficiently small material; (ii) desiccation or preculture on osmotic media to reduce water content; (iii) cryoprotection through exposure to CPAs to promote vitrification; (iv) cryopreservation in LN; (v) re-warming; and finally (vi) the washing (unloading of CPA solutions) and recovery of the germplasm after cryopreservation ( Fig. 1; Funnekotter et al 2017b;Kaczmarczyk et al 2012). There is wide variation in cryo-capability among species, and also among different clonal lines of the same species, therefore each species requires its own cryopreservation protocol to achieve the maximum possible post-cryogenic survival (Reed 2008).…”
Section: Cryopreservation Protocolsmentioning
confidence: 99%
See 3 more Smart Citations